2018
DOI: 10.1016/j.anifeedsci.2018.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of canola meal inclusion as a major protein source in gestation and lactation sow diets with or without enzymes on reproductive performance, milk composition, fecal bacterial profile and nutrient digestibility

Abstract: The objectives of this research were to determine the effects of high inclusion of canola meal (CM) in gestation and lactation diets on lactation performance, milk composition, energy and nutrient digestibility, and gut health in sows and suckling piglet performance. Standardized ileal digestibility (SID) of CP and AA and standardized total tract digestibility (STTD) of P in CM fed to gestating and lactating sows with or without a multi-enzyme complex (MC) was also determined. In Study 1, results showed no dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 188 publications
(351 reference statements)
0
1
0
Order By: Relevance
“…It was revealed that the dehulled rapeseed meal could improve the digestibility of phosphorus but did not alter the bodyweight of pigs [185]. Otherwise, Velayudhan et al [186] studied the impact of incorporating rapeseed meal in sows during gestation and lactation and reported that a ratio of 300 g/kg of rapeseed meal could support sows and suckling piglet performances without negative impacts on nutrient digestibility and energy value, and with a positive impact on the sows' gut lactic acid bacteria. In contrast to pigs, sheep could tolerate high-glucosinolate meals and could be fed with rapeseed meals, with no bad effects on the consumption of the meal, the growth performance and weight of sheep, and milk production [187][188][189].…”
Section: Animal Foddermentioning
confidence: 99%
“…It was revealed that the dehulled rapeseed meal could improve the digestibility of phosphorus but did not alter the bodyweight of pigs [185]. Otherwise, Velayudhan et al [186] studied the impact of incorporating rapeseed meal in sows during gestation and lactation and reported that a ratio of 300 g/kg of rapeseed meal could support sows and suckling piglet performances without negative impacts on nutrient digestibility and energy value, and with a positive impact on the sows' gut lactic acid bacteria. In contrast to pigs, sheep could tolerate high-glucosinolate meals and could be fed with rapeseed meals, with no bad effects on the consumption of the meal, the growth performance and weight of sheep, and milk production [187][188][189].…”
Section: Animal Foddermentioning
confidence: 99%